BmaC, a novel autotransporter of Brucella suis, is involved in bacterial adhesion to host cells - Posadas, D.M. (2012)
Brucella is an intracellular pathogen responsible of a zoonotic disease called brucellosis. Brucella survives and proliferates within several types of phagocytic and non-phagocytic cells. Like in other pathogens, adhesion of brucellae to host surfaces was proposed to be an important step in the infection process. Indeed, Brucella has the capacity to bind to culture human cells and key components of the extracellular matrix, such as fibronectin. However, little is known about the molecular bases of Brucella adherence. In an attempt to identify bacterial genes encoding adhesins, a phage display library of Brucella suis was panned against fibronectin. Three fibronectin-binding proteins of B. suis were identified using this approach. One of the candidates, designated BmaC was a very large protein of 340kDa that is predicted to belong to the type I (monomeric) autotransporter family. Microscopy studies showed that BmaC is located at one pole on the bacterial surface. The phage displaying the fibronectin-binding peptide of BmaC inhibited the attachment of brucellae to both, HeLa cells and immobilized fibronectin in vitro. In addition, a bmaC deletion mutant was impaired in the ability of B. suis to attach to immobilized fibronectin and to the surface of HeLa and A549 cells and was out-competed by the wild-type strain in co-infection experiments. Finally, anti-fibronectin or anti-BmaC antibodies significantly inhibited the binding of wild-type bacteria to HeLa cells. Our results highlight the role of a novel monomeric autotransporter protein in the adhesion of B. suis to the extracellular matrix and non-phagocytic cells via fibronectin binding. © 2012 Blackwell Publishing Ltd.